2017
DOI: 10.18632/oncotarget.21796
|View full text |Cite
|
Sign up to set email alerts
|

Effects of baicalein on IL-1β-induced inflammation and apoptosis in rat articular chondrocytes

Abstract: In osteoarthritis (OA), activated synoviocytes and articular chondrocytes produce pro-inflammatory cytokines, such as IL-1β, that promote chondrocyte apoptosis and activate the NF-κB signaling pathway to induce catabolic factors. In this study, we examined the anti-inflammatory and anti-apoptotic effect of baicalein on IL-1β signaling and NF-κB-regulated gene products in rat chondrocytes. Rat chondrocytes were pretreated with 10 ng/ml IL-1β for 24 h and then co-treated with 10 ng/ ml IL-1β and 50 μM baicalein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…IL-1β is involved in the pathogenesis of OA and it may result in marked alterations to the cartilage, including matrix degradation, inflammation, chondrocyte phenotypic changes and chondrocyte apoptosis ( 26 , 37-39 ). Previous studies have reported that 10 ng/ml IL-1β induces an inflammatory response in chondrocytes ( 27 , 40 ); therefore, 10 ng/ml was used as the working concentration of IL-1β in the present study. IL-1β induces iNOS and COX-2 expression, promotes the synthesis of inflammatory mediators, including prostaglandin E2 and nitric oxide, and stimulates articular chondrocytes to produce high levels of NF-κB ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-1β is involved in the pathogenesis of OA and it may result in marked alterations to the cartilage, including matrix degradation, inflammation, chondrocyte phenotypic changes and chondrocyte apoptosis ( 26 , 37-39 ). Previous studies have reported that 10 ng/ml IL-1β induces an inflammatory response in chondrocytes ( 27 , 40 ); therefore, 10 ng/ml was used as the working concentration of IL-1β in the present study. IL-1β induces iNOS and COX-2 expression, promotes the synthesis of inflammatory mediators, including prostaglandin E2 and nitric oxide, and stimulates articular chondrocytes to produce high levels of NF-κB ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…As previously described (27), cartilage debris was isolated with trypsin (Gibco; Thermo Fisher Scientific, Inc.) at 37˚C for 30 min, and subsequently rinsed with PBS containing penicillin and streptomycin solution. The tissue was digested with collagenase Type II (Gibco; Thermo Fisher Scientific, Inc.) in PBS at 37˚C for 4 h. Subsequently, the supernatant was collected and centrifuged at 500 x g, 27˚C for 7 min.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, HA/CNP can be used to inhibit the NF-κB pathway by increasing IκB. Moreover, Li et al have proved that inhibiting phosphorylated P65 translocation to the nucleus can promote the effect of baicalein against chondrocyte inflammation and apoptosis ( 22 ). Therefore, inhibiting P65 translocation to the nucleus may be a target for OA therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Baicalein is a flavonoid (5,6,7-trihydroxyflavone) that is isolated from the roots of Scutellaria baicalensis and Scutellaria lateriflora and has medicinal properties, including neuroprotective, anti-oxidant, anti-fibrosis, and anti-cancer properties [ 40 , 41 ]. Recently, it has been demonstrated that baicalein has anti-catabolic and anti-apoptotic effects through inhibiting IL-1β induction in chondrocytes [ 42 , 43 ]. Another study showed that the intra-articular injection of medium and high doses of baicalein alleviated OA progression in a rabbit OA model, diminishing cartilage degradation, and showing a lower Mankin score [ 44 ].…”
Section: Natural-compound-based Treatments For Oa Therapymentioning
confidence: 99%